PEMBENAHAN MANAJEMEN UKM KELOMPOK PETERNAK AGRI MAKMUR DAN KELOMPOK PETERNAK ACAP DI DISTRIK PRAFI KABUPATEN MANOKWARI - SONBAIT, LUKAS YOWEL; WIDAYATI, TRISIWI WAHYU (Buletin Udayana Mengabdi; Vol 14 No 1 (2015): April 2015, 2015)
This Ipteks’ activities for society (IbM) have purpose to identify the real problem faced by farmers group AgriMakmur and farmers group Acep in beef cattle cultivation. Methods offered to societies to solve conflicts between groups and improve management in each farmer group. Each group was given record-training about how to manage good business and sustainable finance management therefore standard of group management can be improved. This method is expected to increase trust from members to team leaders from each group. Moreover, societies was offered some simple training about how to do daily standardised form/ standardized report with considering the education level of members so groups’ management qualit. This was hoped to make better and create good communication among members’ group. It was also to increase group performance and develop cattle of livestock population and the last one improve group farmer’s walfare. The result shows that both AgriMakmur and Acap farmers’ group have improved knowledge (Cognitive), skill (Psycho-motoric ) and Attitude ( Affective ) in Cultivation management especially in managed skill of beef cattle, daily note/recording, business analysis and avoiding of conflicts among members and group. Keywords: group management, training, beef cattle